ChemInform Abstract: A New Approach to Prepare Nanoscopic Rare Earth Metal Fluorides: The Fluorolytic Sol—Gel Synthesis of Ytterbium Fluoride. Issue 33 (19th August 2014) - Schmidt, L.; Dimitrov, A.; Kemnitz, E.
Abstract Highly transparent ytterbium fluoride sols of high concentration and low viscosity are prepared by the fluorolytic sol—gel synthesis.